Astragalus propinquus schischkin and Salvia miltiorrhiza bunge promote angiogenesis to treat myocardial ischemia via Ang-1/Tie-2/FAK pathway - Zhang, Mu-Xin; Huang, Xue-Ying; Song, Yu; Xu, Wan-Li; Li, Yun-Lun; Li, Chao (Frontiers in Pharmacology, 2023)
Astragalus propinquus Schischkin and Salvia miltiorrhiza Bunge (AS) have been clinically used as adjunctive drugs in the treatment of myocardial ischemia (MI). However, the effect and mechanism of AS on MI have yet to be fully recognized. Here, we explored the cardioprotective effect of their combined use, and the mechanism of promoting angiogenesis through pericyte recruitment. Our data revealed that AS reduced MI and protects cardiac function. AS-treated MI mice exhibited reduced ST-segment displacement and repolarization time, increased ejection fraction, and less BNP and NT-proBNP expression. Pathological studies showed that, AS reduced the area of infarcted myocardium and slowed down the progress of cardiac remodelling and fibrosis. In addition, AS increased the content of platelet-derived growth factor receptors β (PDGFR-β), platelet endothelial cell adhesion molecule-1 (CD31) and angiogenesis-related proteins including vascular endothelial cadherin (VE-cadherin), Vascular Endothelial Growth Factor (VEGF) and transforming growth factor β (TGF-β). Moreover, these botanical drugs upregulated the expression of Angiopoietin-1 (Ang-1), phosphorylated angiopoietin-1 receptor (p-Tie-2), focal adhesion kinase (FAK) and growth factor receptor bound protein 7 (GRB7), indicating that the cardioprotection-related angiogenesis effect was related to pericyte recruitment, which may be through Ang-1/Tie-2/FAK pathway. In summary, AS can treat MI by protecting cardiac function, attenuating cardiac pathological changes, and hindering the progression of heart failure, which is related to angiogenesis after pericyte recruitment. Therefore, AS at a certain dose can be a promising treatment for MI with broad application prospects.